2019
DOI: 10.1080/02786826.2019.1664724
|View full text |Cite
|
Sign up to set email alerts
|

Real-time sensing of bioaerosols: Review and current perspectives

Abstract: Detection of bioaerosols, or primary biological aerosol particles (PBAPs), has become increasingly important for a wide variety of research communities and scientific questions. In particular, real-time (RT) techniques for autonomous, online detection and characterization of PBAP properties in both outdoor and indoor environments are becoming more commonplace and have opened avenues of research. With advances in technology, however, come challenges to standardize practices so that results are both reliable and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
158
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 189 publications
(162 citation statements)
references
References 241 publications
(260 reference statements)
2
158
0
2
Order By: Relevance
“…It has been shown that a real-time monitoring of pollen with a high temporal resolution can be achieved on what is currently a limited scale (Crouzy et al 2016). Much effort is also being invested in improving autonomous detection of potential allergen-containing particles in real time (Huffman et al 2019;Wu et al 2018 Kiselev, Bonacina, and Wolf 2013). However, there is still need for proving that new methodological approaches are robust enough for continuous longterm outdoor monitoring.…”
Section: Airborne Allergen-containing Particlesmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that a real-time monitoring of pollen with a high temporal resolution can be achieved on what is currently a limited scale (Crouzy et al 2016). Much effort is also being invested in improving autonomous detection of potential allergen-containing particles in real time (Huffman et al 2019;Wu et al 2018 Kiselev, Bonacina, and Wolf 2013). However, there is still need for proving that new methodological approaches are robust enough for continuous longterm outdoor monitoring.…”
Section: Airborne Allergen-containing Particlesmentioning
confidence: 99%
“…Aside from high sample volumes, good practices include stringent cleaning, sterilization, or baking of the sampling equipment (Dommergue et al 2019;Santl-Temkiv et al 2017;Santl-Temkiv et al 2018;Lever et al 2015), sterile techniques when handling and analyzing the samples ( Santl-Temkiv et al 2013; Temkiv et al 2012) as well as performing periodical handling-and operational blanks to verify that measurements are not influenced by contamination (Dommergue et al 2019;Santl-Temkiv et al 2017;Temkiv et al 2012). Finally, using real-time samplers (e.g., fluorescence or mass spectrometric analyzers) as a component of the study can complement other work by providing qualitative or semi-quantitative results at a much higher time resolution (Huffman et al 2019). These methods can also offer real-time windows into atmospheric processes that can help inform the sampling strategy for lower resolution devices, though all techniques that rely primarily on light scattering or chemical information suffer from lower specificity.…”
Section: Issues Related To Bioaerosol Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent developments in UV-LIF technology have allowed real-time detection of bioaerosols, whereby spectral patterns correlate with specific particle characteristics (Huffman et al, 2019). This technology utilises the intrinsic fluorescent properties found within organic molecules, including proteins, co-enzymes, cell wall compounds and certain pigments to differentiate https://doi.org/10.5194/acp-2020-157 Preprint.…”
Section: Wibsmentioning
confidence: 99%
“…Beyond the issue of public health, the airborne transport of pollen plays a key role in ecosystem dynamics, with important implications for agriculture, forestry, and the geographic dispersion of plants (Garzia-Mozo, 2011;Oteros et al, 2014). The relevance of pollen and other bioaerosols for atmospheric chemistry and physics has also been increasingly acknowledged since they represent a significant fraction of atmospheric particulate matter and have been shown to influence cloud formation and precipitation (Jaenicke, 2005;Pöschl, 2005;Möhler et al, 2007;Deguillaume et al, 2008;Pope, 2010). Furthermore, in the context of climate change, pollen concentrations undergo fluctuations in terms of taxa, abundance, and seasonal trends.…”
Section: Introductionmentioning
confidence: 99%